Screening pepper (Capsicum annuum L.) cultivars for resistance against Fusarium wilt disease in Yola, Adamawa State, Nigeria - Ishaku Bajon, Chimbekujwo; Bawa Gambo, Zakari; Adamu Ishaku , Gali (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Pepper (Capsicum spp.) cultivation in Nigeria faces significant challenges due to the prevalence of fungal diseases. This study aimed to screen pepper cultivars for resistance to Fusarium wilt disease. The study was conducted in Yola, Adamawa State, Nigeria from September 2023 to June 2024. The research incorporated a field survey to assess the disease dynamics, laboratory investigations, and screening of pepper cultivars in the screen house. Results from the survey revealed varying levels of incidence and severity of the disease across eight study sites, with Bugare having the highest incidence (41.3%) and severity (25.6 %) of the disease, followed by Ngorore with 34.7 % incidence and 23.4% severity. Geriyo recorded the lowest incidence and severity, with an incidence of 16.7% and severity of 12.5%. Fusarium solani and Fusarium oxysporum were the fungi isolated from the diseased samples. Pathogenicity test confirmed that these pathogens were capable of inducing typical symptoms of the disease on pepper. Significant differences (p=0.05) were observed among the ten pepper cultivars screened for resistance to the pathogens under laboratory and screen house conditions. Cultivar TDKS showed the highest susceptibility to Fusarium infections, with 100% incidence and 56.7% severity on detached fruits, ranked 5 on 0-5 scale, and rated highly susceptible. Infections covered less than 50% of the fruit surfaces on cultivars TDZR, TDBN, ADKS, and SDGJ, each ranked 3 on 0-5 scale and rated moderately resistant. The cultivar ADGE ranked 2 was and rated resistant. None of the cultivars evaluated were completely immune to the pathogens under laboratory condition. Cultivar TDZR, ADGE, TDKS, TDBN, ADKS, and SDGJ were selected for the screen house experiment based on their low disease ranking. Cultivar TDZR, ADGE, and SDGJ were found to be resistant to F. oxysporium (<20 DSI), and moderately resistant to F. solani (20-39 DSI), while cultivar TDBN was moderately resistant to both pathogens under screen house conditions. Based on the results of this study, it can be concluded that there is a high prevalence and severity of Fusarium wilt disease on pepper caused by Fusarium oxysporum, and Fusarium solani in the study areas. Cultivar Tattase Dan Zaria (TDZR) was the most tolerant pepper cultivar to the disease and could be used as a source of resistance in breeding programs to develop Fusarium wilt resistant pepper varieties.